A theory of musical semiotics - Tarasti, Eero (Bloomington Indiana University Press, 1994)
"Since [Tarasti's] is unquestionably the most fully developed narrative theory in the literature, this book is an important landmark... " Music & LettersEero Tarasti advances a semiotic theory of music based on information provided by the history of Western music and by various sign theories. ?A Theory of Musical Semiotics provides a model for the semiotic analysis of both musical structure and semantics. It introduces English-language readers to musical narratology, which has been largely the province of European researchers.